2009
DOI: 10.1002/btpr.190
|View full text |Cite
|
Sign up to set email alerts
|

Promoting α‐secretase cleavage of beta‐amyloid with engineered proteolytic antibody fragments

Abstract: Deposition of beta-amyloid (A beta) is considered as an important early event in the pathogenesis of Alzheimer's Disease (AD), and reduction of A beta levels by various therapeutic approaches is actively being pursued. A potentially non-inflammatory approach to facilitate clearance and reduce toxicity is to hydrolyze A beta at its alpha-secretase site. We have previously identified a light chain fragment, mk18, with alpha-secretase-like catalytic activity, producing the 1-16 and 17-40 amino acid fragments of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 59 publications
(69 reference statements)
0
12
0
Order By: Relevance
“…We have shown that a proteolytic scFv with α-secretase-like activity can promote non-amyloidogenic processing of APP and reduce toxicity in 7PA2 cells. 44 A bispecific antibody construct combining iBSEC1, which inhibits BACE activity and amyloidogenic processing of APP, with an α-secretase-like catalytic scFv, which promotes non-amyloidogenic processing of APP substrates, would allow a single therapeutic molecule to process multiple APP substrates through the nonamyloidogenic pathway (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that a proteolytic scFv with α-secretase-like activity can promote non-amyloidogenic processing of APP and reduce toxicity in 7PA2 cells. 44 A bispecific antibody construct combining iBSEC1, which inhibits BACE activity and amyloidogenic processing of APP, with an α-secretase-like catalytic scFv, which promotes non-amyloidogenic processing of APP substrates, would allow a single therapeutic molecule to process multiple APP substrates through the nonamyloidogenic pathway (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…The specificity constant, (k cat /K M ), toward the A substrate for ASec-1A is 5.6-fold greater and for ASec-1B is 2.8-fold greater than the parent scFv. The increase in activity against A for both scFvs is due to decreases in K M compared to the c23.5 scFv, rather than increases in k cat [67] . The A fragments generated by proteolytic cleavage have a decreased tendency to aggregate and induce cytotoxicity compared to the full length A [57].…”
Section: Proteolytic Antibody Fragments For Clearance Of Amentioning
confidence: 85%
“…Following bio-panning, isolated single clones were screened for proteolytic activity against a fluorogenic A substrate. Two clones (Asec-1A and Asec-1B) with improved proteolytic activity compared to the parent clone were identified [67]. The cleavage products of A 40 substrate with both scFvs were similar to those of the parent mk18 light chain antibody as determined by mass spectrometry, with A 1-16 as the predominant product (Fig.…”
Section: Proteolytic Antibody Fragments For Clearance Of Amentioning
confidence: 97%
See 1 more Smart Citation
“…We found the addition of the LDLR binding domain of ApoB, in addition to improving BBB transport, facilitated neuronal and glial cell uptake through the LDLR receptor leading to endosomal sorting complex required for transport (ESCRT) mediated endocytosis and autophagosome degradation thus bypassing the Fc receptor signaling cascade that could lead to cytotoxicity (Spencer et al, unpublished). scFV antibodies targeted to Aβ could be used with this approach to target AD (Liu et al, 2004; Fukuchi et al, 2006; Kasturirangan et al, 2009; Kasturirangan and Sierks, 2010). …”
Section: Future Directionsmentioning
confidence: 99%